Estimation of Sea Spray Aerosol Surface Area Over the Southern Ocean Using Scattering Measurements. Issue 22 (20th November 2022) - Moore, Kathryn A.; Alexander, Simon P.; Humphries, Ruhi S.; Jensen, Jorgen; Protat, Alain; Reeves, J. Michael; Sanchez, Kevin J.; Kreidenweis, Sonia M.; DeMott, Paul J.
Abstract: This study focuses on methods to estimate dry marine aerosol surface area (SA) from bulk optical measurements. Aerosol SA is used in many models' ice nucleating particle (INP) parameterizations, as well as influencing particle light scattering, hygroscopic growth, and reactivity, but direct observations are scarce in the Southern Ocean (SO). Two campaigns jointly conducted in austral summer 2018 provided co‐located measurements of aerosol SA from particle size distributions and lidar to evaluate SA estimation methods in this region. Mie theory calculations based on measured size distributions were used to test a proposed approximation for dry aerosol SA, which relies on estimating effective scattering efficiency ( Q ) as a function of Ångström exponent ( å ). For distributions with dry å < 1, Q = 2 was found to be a good approximation within ±50%, but for distributions with dry å > 1, an assumption of Q = 3 as in some prior studies underestimates dry aerosol SA by a factor of 2 or more. We propose a new relationship between dry å and Q, which can be used for −0.2 < å < 2, and suggest å = 0.8 as the cutoff between primary and secondary marine aerosol‐dominated distributions. Application of a published methodology to retrieve dry marine aerosol SA from lidar extinction profiles overestimated aerosol SA by a factor of 3–5 during these campaigns. Using Microtops aerosol optical thickness measurements, we derive alternative lidar conversion parameters from our observations, applicable to marine aerosol over the SO. Plain Language Summary: The Southern Ocean (SO) surrounding Antarctica is one of the few places where aerosol concentrations and composition are similar to pre‐industrial values. This makes data collected in this region important for improving and understanding climate model simulations. However, direct observations of aerosols are rare because of the remoteness, frequent storms, and high winds and waves common to the SO. In this study, we use some of these rare aerosol observations to test methods for estimating important aerosol quantities using other measurements that are easier to collect. The improvements presented here may increase the availability of key data for improving climate models by replacing rare measurements with ones that can be collected continuously and autonomously. Key Points: Methods to estimate dry marine aerosol surface area (SA) from bulk optical measurements were tested for the Southern Ocean region A new relationship between effective scattering efficiency and dry Ångström exponent is proposed for nephelometer measurements Overestimation of aerosol SA from previous methods is reduced by derivation of new lidar backscatter conversion parameters